Framework for overseas expansion : exploring the decisions of SMEs in Singapore. - Leong, Amanda. (2012)
Due to the increasing emphasis on international business, this study aims to develop a systematic approach to help these SMEs in their decision process for overseas expansion, in the form of a general framework. We conducted secondary research to develop the initial framework, encompassing the decision points that our research indicated as important. These are the Rate of Entry, the Operational Mode, as well as the Location of Entry. Additionally, it is implied in our framework that there is no specific sequence between the various decision points. Lastly, based on the research, we also derived flowcharts for each of the identified point, highlighting the important considerations. Next, we interviewed business professionals from SMEs in different industries to validate our framework. The final outcome is an improved framework and a set of flowcharts which we have been able to apply successfully to a fictitious SME using two different scenarios. While the framework and flowcharts do not really lessen the information a company needs to collect and analyze before expanding abroad, it does provide a systematic approach, and gives companies an overview of what is needed, ensuring that all the important factors are covered. As this study is exploratory in nature, further quantitative studies can be conducted to substantiate the correlation between the different factors within each flowchart. Further studies can also be conducted to see if the framework and flowcharts will apply to big MNCs as well. Additionally, this study highlights that some companies are innately different and do not find it necessary to apply any framework or flowcharts to aid in their decision process. Also, it highlights the point that importance of considering whether a company will physically locate some/all operations abroad depends on the company itself.